2013
DOI: 10.1590/s0102-311x2013000600007
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between low birth weight and exposure to inhalable particulate matter

Abstract: Atmospheric pollution is a global public health problem. The adverse effects of air pollution are strongly associated with respiratory and cardiovascular diseases and, to a lesser extent, with adverse pregnancy outcomes. This study analyzes the relationship between exposure to PM10 and low birth weight in the city of Santo André, São Paulo State, Brazil. We included babies born to mothers resident in Santo André between 2000 and 2006. Data on daily PM10 levels was obtained from the São Paulo State Environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
0
9
0
11
Order By: Relevance
“…Studies that have evaluated placental vascularization in the first trimester and have predicted pregnancy complications observed that women with diminished VI and VFI showed an increased tendency to have pregnancies that were later complicated with preeclampsia and fetal growth restriction (de Almeida Pimenta et al 2014; Odeh et al 2011; Odibo et al 2011). Short-term exposure to air pollution seems to affect the same indexes, which indicates the possible pathway by which air pollution may provoke these complications (Olsson et al 2013; Pedersen et al 2014; Romão et al 2013; Sapkota et al 2012; Shah et al 2011; van den Hooven et al 2011; Yorifuji et al 2015). …”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Studies that have evaluated placental vascularization in the first trimester and have predicted pregnancy complications observed that women with diminished VI and VFI showed an increased tendency to have pregnancies that were later complicated with preeclampsia and fetal growth restriction (de Almeida Pimenta et al 2014; Odeh et al 2011; Odibo et al 2011). Short-term exposure to air pollution seems to affect the same indexes, which indicates the possible pathway by which air pollution may provoke these complications (Olsson et al 2013; Pedersen et al 2014; Romão et al 2013; Sapkota et al 2012; Shah et al 2011; van den Hooven et al 2011; Yorifuji et al 2015). …”
Section: Discussionmentioning
confidence: 86%
“…However, because placental indexes correlate with real vascularization and flow (Morel et al 2010; Pairleitner et al 1999; Raine-Fenning et al 2008a), our results suggest that these factors are diminished when the mother is exposed to higher values of NO 2 . Diminished placental vascularization may be the underlying cause of the impaired fetal growth and adverse pregnancy outcomes are related to higher levels of air pollution exposure during pregnancy (Olsson et al 2013; Pedersen et al 2013, 2014; Romão et al 2013; Sapkota et al 2012; Shah et al 2011; van den Hooven et al 2011, 2012; Yorifuji et al 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…V). A significant association between risk of low birth weight and exposure to pollutants was found, like PM 10 , CO [98,112,118], SO 2 and O 3 [107]. A research [108] also revealed a gradient of approximately 50% of increasing risk of early neonatal death with higher exposure to traffic-related air pollution, compared with those less exposed.…”
Section: Regional -Regional Environmental Factorsmentioning
confidence: 84%
“…Praticantes de exercícios em locais com elevadas concentrações de material particulado podem ter redução de suas funções pulmonares (KESAVACHANDRAN et al, 2015). Os efeitos adversos da exposição ao particulado inalável vão além das doenças cardiorrespiratórias, pois aumentam o risco de recém-nascidos com baixo peso (ROMÃO et al, 2013). E há inclusive estudos que relatam associação entre o nível de PM10 e a mortalidade (BLANCO-BECERRA et al, 2014;CESARONI et al, 2013).…”
Section: Introductionunclassified